A numerical investigation of heat transfer performance in a prismatic battery cooling system using hybrid nanofluids - B. Venkateswarlu; Santosh Chavan; Sang Woo Joo; Sung Chul Kim; Kottakkaran Sooppy Nisar (Case Studies in Thermal Engineering)
The increasing demand for high-performance batteries in electric vehicles and energy storage solutions has driven substantial research focused on enhancing the thermal management of battery packs. This study presents a numerical investigation of the heat transfer performance in a prismatic battery cooling system that employs hybrid nanofluids. The cooling system is designed to maintain optimal operating temperatures by circulating the hybrid nanofluids through microtubes serving as cooling channels. The governing flow model equations for momentum and energy are derived based on the microtube cooling channel of the battery structure, incorporating convection, heat generation, and viscous dissipation. Further, numerical simulations are performed for the model equation using the shooting process algorithm in MATLAB software. The results are analyzed to evaluate the coolant temperature, flow behavior, and heat transfer efficiency of the nanofluids surrounding the battery under varying factors. The findings reveal that heat generation causes the Cu-Al2O3/H2O hybrid nanofluid to experience a significant 4.12 % decrease in battery temperature compared to the Al2O3/H2O nanofluid. The liquid flow rate increased by 5.5 % with the increase in nanoparticle volume fraction, while the battery temperature showed a significant decrease of 7.13 % for hybrid nanofluids. The hybrid nanofluid exhibited a faster battery surface heat transfer rate of 5.86 % compared to the nanofluid, due to its superior thermal properties from the hybrid nanoparticles. This research highlights the potential of hybrid nanofluids as an effective coolant for enhancing the heat transfer performance of battery modules in electric vehicles and energy storage applications.